2008
DOI: 10.1542/peds.2007-1571
|View full text |Cite
|
Sign up to set email alerts
|

Motivations of Mothers to Enroll Their Newborn Infants in General Clinical Research on Well-Infant Care and Development

Abstract: There is some willingness to consent when the infant is healthy and the research is not directed at solving a specific problem of the infant. The degree of consent decreases in accordance with the increase in risk. The altruistic motive is the main predictor for research that is perceived as very risky. The benefit of learning about their infant's development served as a motivating force for less risky studies. We deduce that pointing out personal benefits to balance the usual conveyed information on risks or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 14 publications
5
39
0
Order By: Relevance
“…Similar to our findings, previous studies found that most important motives for parents to consent for research on their children were: clear benefit to their child; detailed explanation on the research consent form; and the research adding to medical knowledge [11,12,18,19]. In a survey of parents of children with leukaemia, the most frequently suggested factors to improve informed consent were: giving parents more time to make their decision; the amount and type of information provided; organization of the consent conference; communication style; and providing additional information materials [20].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our findings, previous studies found that most important motives for parents to consent for research on their children were: clear benefit to their child; detailed explanation on the research consent form; and the research adding to medical knowledge [11,12,18,19]. In a survey of parents of children with leukaemia, the most frequently suggested factors to improve informed consent were: giving parents more time to make their decision; the amount and type of information provided; organization of the consent conference; communication style; and providing additional information materials [20].…”
Section: Discussionsupporting
confidence: 91%
“…The finding was evident and in line with previous studies [9,10]. Promotion of the common good and public health was the second most important reason to participate.…”
Section: Discussionsupporting
confidence: 90%
“…The possible risks of trials have commonly been reported to be the dominating cause for declining consent [5,6,9,12,14]. For the present questionnaire, the safety concerns may have been even further inflated due to the special media attention on the association between pandemic flu vaccine and narcolepsy [15] at the time of the questionnaire study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, it is unlikely that developmental or behavioural problems were under-or overestimated in our study. Since the The rate ratio (RR) estimates of birth in level III hospital are adjusted for intrauterine growth, multiple births, sex, gestational age, birthweight, non-lethal malformations, the mother's and the father's years of education and employment status, and family structure p values are given with adjustments for intrauterine growth, multiple births, sex, gestational age, birthweight, non-lethal malformations, the mother's and the father's years of education and employment status, and family structure The rate ratio (RR) estimates for birth outside office hours are adjusted for intrauterine growth, multiple births, sex, gestational age, birthweight, non-lethal malformations, the mother's and the father's years of education and employment status, and family structure mothers of full-term infants have been less willing to participate in trials than mothers of preterm infants [27], we had, as expected, a lower response rate for the controls than for the VLBWI. The parents of VLBWI are more likely to regard this type of study as important than the parents of the controls.…”
Section: Discussionmentioning
confidence: 99%